Current state of populations of Centaurea bipinnatifida in Ulytau Mountains (Karaganda region) - Asanova, G.K. (Fundamental and Experimental Biology, 2022)
The concept of conservation of biological diversity implies the need to study the state of plant populations that grow limited in nature and have a tendency to decline. In the Karaganda region, the list of rare species and local narrow endemics includes Centaurea bipinnatifida, whose habitation is confined to the Ulytau Mountains. To assess the state of 3 populations of this species, their ecological and phytocenotic structure, botanical features, morphometric indicators of plants, and the ratio of ontogenesis phases were studied. This species is confined to steppe and meadow-steppe areas in the foothills of Ulytau, less oftenlives along crushed and rocky gentle slopes. It was determined that the species composition of communities had from 41 to 51 species. The largest number of species is concentrated in families Asteraceae, Rosaceae, Poaceaeбand Fabaceae. Mesophytes dominated among ecological groups, herbaceous perennials predominated among life forms. The analysis of the morphometric parameters and age spectrum of Centaurea bipinnatifidamade it possible to determine that the entire population is characterized as stable young and medium-age witha predominance of young or medium-age generative plants. Based on the field surveys one can recommend the development of a population monitoring program to maintain their structure and preserve the species under natural conditions.